Nursing Students’ Perceptions and Attitudes regarding Ebola Patients in South Africa - Manyisa, Zodwa Margaret; Osuafor, G. N.; Akinsola, H. A. (Africa Journal of Nursing and Midwifery, 2019)
There is an association between the perceptions of and the attitudes to the willingness of nursing students to treat infectious diseases. However, this relationship between the perceptions, attitudes and willingness to treat rapidly spreading diseases with high fatality rates such as the Ebola virus is still evolving. The aim of this study was to explore and describe nursing students’ perceptions of and attitudes to their willingness to treat Ebola patients in South Africa. Data were collected from 495 nursing students who voluntarily participated in a study on perceptions, attitudes and willingness to treat patients with the Ebola virus disease (EVD). A factor analysis was used to measure the association between nursing students’ perceptions of and attitudes to their willingness to treat patients with EVD. The results showed that 44.8 per cent of the respondents expressed willingness to nurse patients with EVD. The willingness to care for patients with EVD was higher when family concerns and superstitious beliefs did not matter. Incentives and encouraging hospital settings were perceived to enhance a willingness to care for patients with EVD. The willingness to care for patients with EVD was less when a perceived fear of infection was high. To improve a willingness to care for patients with EVD, the identified perceptions and attitudes should be integrated in nurse training programmes. These factors may have a positive impact on the perceptions of and attitudes to caring for patients with EVD.